The Social Dimension of Distance Learning by Interactive Television: A Qualitative Study - Liang Zhao (Arizona State University, 2011)
This qualitative study examined instructorsâ and studentsâ perceptions of social relationship in distance learning. Interview and observational data were collected and analyzed to generate theories. Factors influencing a sense of distance were analyzed. Findings revealed greater difficulty establishing a social relationship in interactive television environments than in face-to-face environments. Both instructors and students found it more important to build a personal connection between them. Instructorsâ preference for course delivery and building rapport with students was to travel and teach at the remote sites. The study implies that faculty and administrators should seriously consider, in their decision-making, both the gains and losses of interactive television as a delivery format.